A review of mate‐finding Allee effects in insects: from individual behavior to population management. Issue 1 (4th December 2012) - Fauvergue, Xavier
Abstract Like other animals and plants, insects may find it difficult to survive and reproduce in small populations, to the extent that their long‐term persistence may be jeopardized. The Allee effect is a theoretical framework that formalizes this decrease in survival or reproduction in small populations, and the resulting decrease in population growth and persistence. Mating failure in low‐density populations is likely to generate an Allee effect and, therefore, has a major effect on the functioning of small populations. Here, I review mate‐finding Allee effects in insect species, and their consequences for individual mating success, population dynamics, and population management. I focus, in particular, on the comparison of theoretical expectations with observational data. Several studies have reported some degree of mating failure at low density. However, almost none of the datasets available allow comparison with the predictions of classical mate‐searching models. A few studies at the population level have reported the co‐occurrence of mating failure at low density and a demographic Allee effect, but no study has yet clearly demonstrated a causal relationship between mating failure and lower rates of population growth. Thus, although the theoretical development of management tactics based on Allee effects is considered promising, the current lack of evidence supporting this strategy limits its potential relevance. I call here for a more rigorous approach to the study of mate‐finding Allee effects and propose new approaches for this purpose.